Recommendations on Off-Label Drug Use in Pediatric Guidelines - Meng, Min; Zhou, Qi; Lei, Wenjuan; Tian, Min; Wang, Ping; Liu, Yunlan; Sun, Yajia; Chen, Yaolong; Li, Qiu (Frontiers in Pharmacology, 2022)
Objective: To systematically analyze the supporting evidence, drug information, and forms of off-label drug use in recommendations on off-label drug use in pediatric guidelines. Methods: A cross-sectional study was performed by systematic search through MEDLINE (via PubMed) and Embase databases to identify literature published from January 1, 2018, to December 31, 2020. Only pediatric clinical practice guidelines that included recommendations on off-label use of drugs were included. We present descriptive information on the sources of the included guidelines, country, publication year, evidence grading system used, details on the types of off-label drug use, and the types of studies used as references to support the recommendations. Results: A total of 66 pediatric guidelines with 605 recommendations were included. Eighty-seven (14.4%) recommendations did not cite any references; and the remaining 518 recommendations were supported by 2240 references (mean 4.3 references/recommendation). The most common types of studies cited were pediatric RCTs (n=314, 14.0%), pediatric case series studies (n=260, 11.6%), and reviews (n=255, 11.4%). Twenty-one percent (n=470) of the references were studies on adults. One hundred and forty (23.1%) recommendations were graded using the Grading of Recommendations, Assessments, Development, and Evaluations (GRADE) system, of which 37 (26.4%) were graded as strong but supported with only C or D level of evidence. The most commonly reported type of information in the recommendations was indication (n=499, 82.5%). The most commonly addressed type of off-label drug use in the 523 positive recommendations was unapproved population (n=255, 48.8%). Sixty-nine (11.4%) recommendations explicitly reported the drug use as off-label. Conclusions: Children may be exposed to medical risks due to gaps in reporting and evidence of off-label drug use recommendations in pediatric guidelines.